Resveratrol protects mitochondrial quantity by activating SIRT1/PGC‐1α expression during ovarian hypoxia. (16th March 2020) - Nishigaki, Akemi; Kido, Takeharu; Kida, Naoko; Kakita‐Kobayashi, Maiko; Tsubokura, Hiroaki; Hisamatsu, Yoji; Okada, Hidetaka
Abstract: Purpose: Resveratrol is a well‐known potent activator of sirtuin‐1 (SIRT1). We investigated the direct effects of hypoxia and resveratrol on SIRT1/ peroxisome proliferator‐activated receptor‐gamma coactivator 1α (PGC‐1α) pathways, vascular endothelial growth factor (VEGF), hypoxia‐inducible factor (HIF)‐1α, and mitochondrial quantity in a steroidogenic human ovarian granulosa‐like tumor cell line (KGN) cells. Methods: KGN cells were cultured with cobalt chloride (CoCl2 ; a hypoxia‐mimicking agent) and/or resveratrol. The mRNA and protein levels, protein secretion, and intracellular localization were assessed by real‐time PCR, Western blot analysis, ELISA, and immunofluorescence staining, respectively. Mitochondrial quantity was measured based on the mitochondrial DNA (mtDNA) copy number. Results: CoCl2 simultaneously attenuated the levels of SIRT1 and mtDNA expression, and induced the levels of VEGF protein production. In contrast, resveratrol significantly increased the levels of SIRT1 and mtDNA copy number, but reduced VEGF production in normoxia. Resveratrol could recover CoCl2 ‐suppressed SIRT1 and mtDNA expression and antagonize CoCl2 ‐induced VEGF production. CoCl2 treatment resulted in a downregulation of PGC‐1α expression, and this effect was recovered by resveratrol. Resveratrol significantly suppressed the production of the CoCl2 ‐induced HIF‐1α and VEGF proteins. Conclusion: These results suggest that resveratrol improves mitochondrial quantity by activating the SIRT1/PGC‐1α pathway and inhibits VEGF induction through HIF‐1α under hypoxic conditions. Abstract : Resveratrol improves mitochondrial quantity by activating the SIRT1/PGC‐1α pathway in hypoxia. PGC‐1α was strong and predominantly localized to the nucleus of the cells treated with resveratrol. CoCl2‐reduced PGC‐1α mRNA and protein expression was recovered by resveratrol.